Quality of life of cancer patients in routine clinical care using the example of checkpoint inhibition therapy: a Delphi consensus - Ivanyi, Philipp; Alt-Epping, Bernd; Bullinger, Lars; Gesierich, Anja; Krabbe, Laura-Maria; Münch, Urs; Pfitzner-Dempfle, Susanne; Rieger, Christina; Rittmeyer, Achim; Wiesing, Urban; Wolf, Martin; Hofheinz, Ralf-Dieter (Oncology research and treatment, 2025)
Introduction: The introduction of immune checkpoint inhibitors (CPIs) in oncology has improved the long-term perspectives of many patients and is bringing the quality of life (QoL) into focus as a treatment-relevant variable. In clinical routine, standardized and reliable tools for collecting, understanding, and utilizing QoL information are needed. In the current work, an interdisciplinary consensus on aspects of QoL in standard clinical practice has been put forth. Methods: After independent, structured individual interviews with members of an interdisciplinary expert panel (n = 12), ten theses on QoL with particular consideration regarding CPI therapy were drafted. These formed the basis of a multistage, independent, anonymous, externally commented, qualitative Delphi process. During the period May - December 2022, the panel developed interdisciplinary consensus recommendations for recording QoL and its role in decision-making in everyday care. Results: Out of ten theses, five recommendations arranged into three subject areas were agreed upon. QoL is considered a multifactorial and dynamic parameter that goes far beyond treatment-associated side effects. Mindful communication with the patient is considered the basis for QoL assessment and QoL modification. In everyday clinical practice, QoL should be documented and assessed in a structured, regular, and individualized way, thereby providing a basis for decisions on treatment options. Conclusion: The individual QoL of cancer patients should be assessed before and throughout therapy. Especially for long-term responders of CPI therapy and in the adjuvant setting, QoL appears to be treatment relevant. The recommendations based on the Delphi method provide practical assistance.